Optimization of Drilling Parameters for Enhanced Hole Circularity and Chip Formation in Aircraft Components Manufacturing - Ibrahim, Rasidi; Ahmad, Aishah; Zainoridin, Hadrami; Hong, Chong Bin; Cheng, Kai (Engineering Research: Perspectives on Recent Advances Vol. 4, 2025)
Drilling is a crucial process in the production of accurate holes for aircraft components, but challenges such as poor circularity and unpredictable chip formation in aluminum alloys can compromise airframe quality and introduce potential defects. This study focuses on optimizing chip formation, hole circularity, and drilling parameters, particularly feed rate and spindle speed. Dry drilling experiments were performed using high-speed steel drill bits on Al6061-T6 alloy, with CIMCO MDC-MAX software utilized for monitoring machine performance and collecting detailed data. The research examines the effects of varying feed rates on hole circularity, chip characteristics, and chip thickness. Results show that higher feed rates lead to greater circularity errors and increased chip thickness. Variations in circularity are linked to workpiece vibrations during drilling, while chip thickness increases with feed rates and cumulative drilled holes due to factors such as tool wear and suboptimal cutting conditions. Additionally, a significant relationship between machine performance and product quality is observed. Data from CIMCO MDC-MAX indicate that a feed rate of 0.260 mm/rev achieves superior machine performance and minimal circularity error. Conversely, Drill 6, operating at a feed rate of 0.230 mm/rev, demonstrates lower machine performance and higher average circularity error. These findings provide valuable insights into the interplay between drilling parameters and hole quality, emphasizing the importance of parameter optimization to improve drilling performance in aircraft manufacturing. The study offers practical recommendations for enhancing drilling processes in the production of aircraft components.